"Quem come do meu pirão, apanha do meu cinturão": um estudo com homens autores de violência doméstica e familiar contra as mulheres - Lôbo, Gutierrez Alves (2019)
This paper analyzes how domestic and family violence against women is understood by men who are authors of this violence. Therefore, examines this issue and the gender issues contained therein from the perspective of men who met in hearings in the Court of Domestic Violence and Family Against Women of the city of Campina Grande – Paraíba, in the temporal clipping from September to November 2018. In order to achieve this analysis identifies the cultural historical devices that constitute the vision of men perpetrators of violence against women on this issue; problematize the vision offered by these men in the face of gender issues, emphasizing the aspects related to the construction of their masculinities; discuss whether and how these men are reached by public policies aimed at confronting violence against women. By the nature of its objectives, the research is qualitative in nature, based on bibliographic study and field research. The instruments used for data collection were semi-structured interviews, whose testimonials were addressed from a gender analytic perspective, that make possible think of the discourses as instances that not only demonstrate but, above all, institute the meanings attributed to the relations between genders in our society, with its flow of ruptures and permanences. The analysis carried out leads to the understanding that the discourses of men witnesses are permeated by games of knowledge and power, getting through to appropriating feminist discourse and political agency about gender equality. However, the difficulty of naming the violence of which they are accused prevails, of assuming it as such, commonly creating subterfuges for the guilt of women and or the social system to justify their practices. Many contradictory marks between these and their testimonies indicate the lack of understanding about the broader perspective of what violence is and what they represent in the game of gender relations and in the updating of inequalities. It also considers that the lack of further studies and interventional work with these men ultimately contributes to the increase of impunity in these cases. It is a research that allows the reflection on themes such as gender, masculinities and violence, as well as think about other possibilities of coping with domestic and family violence against women.